Nephrotic Range Proteinuria in Renal Transplantation: Clinical and Histologic Correlates in a 10-year Retrospective Study - Leal, R (2017)
INTRODUCTION: There is a high incidence of nephrotic proteinuria in renal transplant recipients, which is an accurate predictor of graft loss. Despite this, its histologic correlates and prognostic implications are still not well characterized. We assessed the clinical and histological correlates of kidney transplantation patients with nephrotic range proteinuria. METHODS: We have retrospectively analyzed clinical and histological data from 50 kidney transplantation biopsy specimens from 44 renal transplant recipients with nephrotic range proteinuria between 2006 and 2015. The median follow-up time was 93 months (range, 14 months to 190 months). RESULTS: The mean age of the patients was 45.2 ± 13.7 years and our cohort included 86% recipients of deceased-donor grafts. The maintenance immunosuppressive regimen included calcineurin inhibitors in 68% and mammalian target of rapamycin inhibitors in 32% of patients. The average proteinuria was 6.9 ± 3.8 g/d and 52% of patients presented with nephrotic syndrome. The main histological findings were transplant glomerulopathy (22%), de novo glomerular disease (22%), and recurrence of primary disease (22%). Tubular atrophy and interstitial fibrosis was present in 78% of the biopsy specimens. Thirty-one patients (62%) lost the graft at follow-up. There was no statistically significant difference between the histologic diagnosis nor the proteinuria levels and the outcome of the graft. CONCLUSIONS: The main causes of nephrotic range proteinuria in patients undergoing biopsy were transplant glomerulopathy, recurrence of the underlying disease, and de novo glomerulonephritis. Nephrotic range proteinuria was related to a high rate of graft loss.